The influence of growth conditions on strain differentiation within the Lactobacillus acidophilus group using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry profiling - Šedo, Ondrej; Vávrová, Andrea; Vad'urová, Marta; Tvrzová, Ludmila; Zdráhal, Zbyněk (Rapid communications in mass spectrometry, 2013)
RATIONALE: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) profiling of bacteria is often used to distinguish isolates beyond the species level, even to the level of individual strains. However, the influence of bacterial growth conditions on the discriminatory power of the method to the strain level has not yet been properly evaluated. METHODS: For the purpose of this study, we used an extraction protocol recommended for clinical laboratories for MALDI-TOF MS profiling of bacteria. Seventeen closely related strains of the Lactobacillus acidophilus group were cultivated under various growth conditions (growth medium, time, and temperature) and analyzed. RESULTS: Out of a total of 327 samples, 80 % were correctly assigned to the species level and 13 % only to the genus level. When using data obtained from strains cultured for lengthy periods (7 days), the identification success rate was reduced due to poor signal quality, whereas with shorter cultivation times there was no influence of growth conditions on the assignment of particular strains to their corresponding species. However, variations in certain cultivation parameters were found to influence identification and differentiation of most of the examined strains. Strain discrimination was frequently found to be dependent on the selection of culture conditions. MALDI-TOF MS data treatment (strain-specific peak detection, BioTyper scoring, subtyping, or cluster analysis) also contributed to the discriminatory power of the method. CONCLUSIONS: When MALDI-TOF MS profiling of bacteria is used for strain discrimination, the cultivation conditions should be properly optimized and controlled as they significantly contribute to the discriminatory power of the method.
Keywords: Reproducibility of Results; Phylogeny; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Lactobacillus acidophilus; Temperature; Bacterial Typing Techniques; Culture Media; Time; fylogeneze; teplota; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; kultivační média; reprodukovatelnost výsledků; techniky typizace bakterií; čas